Serum Level of Interleukin-35 in Patients with Chronic Hepatitis B Virus Infection - Al-azzawi, Raghad H.; Mohsen, Rana T.; Ad'hiah, Ali H. (Iraqi Journal of Science, 2020)
Interleukin-35 (IL-35) is a new member of IL-12 family of cytokines, and its role in pathogenesis of hepatitis B virus (HBV) infection has been recently suggested. Accordingly, a case-control study was conducted during June - October 2018 to determine IL-35 serum level in Iraqi patients with chronic HBV infection. The results revealed that IL-35 level was significantly decreased in patients as compared to control (163 vs. 301 pg/ml; p < 0.001). However, such decreased level was more pronounced in patients at the age groups < 40 and 40 – 50 years (165 and 145 pg/ml, respectively) as compared to the corresponding age groups in control (482 and 234 pg/ml, respectively). In the case of gender groups, both male and female patients showed a significantly decreased level of IL-35 compared to the corresponding control groups (163 and 163 vs. 306 and 297 pg/ml; p = 0.004 and 0.001, respectively). Distributing HBV patients and control according to medians of IL-35 (≤ median and > median) revealed that 67.5% of patients had ≤ median compared to 35.4% among control. Such difference was significant (p < 0.001), with a scored odds ratio (OR) of 3.79. Receiver operating characteristic (ROC) analysis revealed that the decreased level of IL-35 occupied an area under curve (AUC) of 0.710, which was highly significant (p < 0.001). At a cut-value of 188 pg/ml or lower, the diagnostic sensitivity and specificity were 67.7 and 66.2%, respectively. In conclusion, these results confirmed the role of IL-35 in the pathogenesis of HBV